Increase Women Leaders As a Corporate Performance Drivers In Building Material Company - Izzati, Nailu Nur; Bangun, Madju Yuni Ros (Universitas Nahdlatul Ulama Surabaya, 2023)
SDG 5, or Sustainable Development Goal 5, is one of the 17 goals established by the United Nations in 2015 as part of the 2030 Agenda for Sustainable Development. SDG 5 grants women and girls equal rights and opportunities to live free without discrimination, including workplace discrimination, career opportunities, and violence. The achievement of SDG 5 is critical to creating a sustainable future where women can contribute to society without fear of discrimination. The problem statement in this research is what key success, motivation, and competency are needed for women to become leaders, there are a constraint and perceptions about women that can be barriers to becoming a leader, how support system can help women to become leaders, women have limitations in their career development. The dependent variable in this study is the